"SEPUCHI" CLASS FOR COMMUNITY HEALTH WORKERS AS AN EFFORT TO ENHANCE ELDERLY INTEGRATED HEALTH SERVICES IN DENPASAR - Martini, Ni Made Dwi Ayu; Sari, Ni Luh Putu Dian Yunita; Darmaja, Ketut (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The positive paradigm of aging leads us to healthy and happy aging. Sexual well-being is one of the aspects. Elderly with hypertension are expected to exhibit adaptive behavior towards sexual changes. The SEPUCHI physical exercise, a combination of Kegel and Tai Chi exercises, is beneficial for enhancing the sexual activity of the elderly. The SEPUCHI class program is anticipated to diversify and broaden insights regarding physical exercises suitable for the elderly. This program consists of 3 sessions attended by 10 community health workers. Participants were given pre- and post-class SEPUCHI questionnaires and evaluated using assessment forms. The results indicate that all participants experienced an improvement in knowledge and were able to practice the SEPUCHI physical exercise. It is hoped that the community health workers will implement the SEPUCHI physical exercise in the elderly community health services.